Analysis of the internal replication sequence indicates that there are three elements required for efficient replication of minute virus of mice minigenomes. - Brunstein, J (1997)
Prior analysis of minigenomes of minute virus of mice carried out by our laboratory indicated that sequences within the region of nucleotides 4489 to 4695, inboard of the 5' palindrome, are required for efficient DNA replication of the virus and are the site of specific interactions with unidentified factors present in a host cell nuclear extract (P. Tam and C. R. Astell, Virology 193:812-824, 1993; P. Tam and C. R. Astell, J. Virology 68:2840-2848, 1994). In order to examine this region in finer detail, a comprehensive library of linker-scanning mutants spanning the region was tested for the ability to support replication of minigenome constructs and for the ability to interact with host cell factors. Three short discrete sequence elements critical for replication competence were observed. Binding of host cell nuclear factors was localized to four sites, with two major complexes each appearing to have two binding sites within the region. All factor binding sites were found to be directly adjacent to or overlapping with sequence elements contributing to replication competence, and evidence suggesting a correlation between factor binding and minigenome replication is presented. A possible model is proposed for function of a viral origin within the region of the internal replication sequence which addresses the still-unresolved problem of how parvoviruses overcome the thermodynamic energy barrier involved in the rearrangement of the 5'-terminal palindrome from an extended form to a hairpin conformation.